Does self-compassion protect adolescents with non-suicidal self-injury from developing borderline features? A two-wave longitudinal study - Carreiras, Diogo (2024)
Background: Adolescence is a vulnerable developmental stage for the onset of non-suicidal self-injury (NSSI) and borderline features, which are related psychological phenomena. Self-compassion reflects a sensitivity to own suffering and a motivation to relieve it, consisting of a more positive and beneficial self-to-self relationship. The aim of the present study was to test the effect of self-compassion between borderline features at baseline and six months with a sample of adolescents with a history of NSSI.Methods: At assessment wave one, participants were 139 Portuguese adolescents with an NSSI history (mean age = 15.52 years, SD = 0.87). Of these, 87 were re-assessed six months later (mean age = 15.46 years, SD = 0.86). Data were analysed through SPSS and PROCESS Macro.Results: The moderation model explained 56% of borderline features six months later, and the interaction between initial borderline features and the low and medium levels of self-compassion was significant. Youth with lower initial borderline features presented higher borderline features six months later if they had low self-compassion.Conclusions: These findings suggest that among adolescents with a history of NSSI, those with lower levels of self-compassion tend to exhibit higher borderline features in six-month when compared to their peers with higher levels of self-compassion. This observation emphasises the potential beneficial effect of self-compassion within this population.